Strangulation of Heart Due to Calcified Constrictive Pericarditis Causing Right Heart Failure - Talukder, Md Faisal; Hongxin, Li; Fei, Liang (Cardiology and Cardiovascular Medicine, 2020)
Background: Constrictive Pericarditis (CP) results from fibrosis and calcification of pericardium. CP can be present with the assemblage of symptoms due to strangulation of heart. However, right heart failure due to localized calcified CP is exceptionally unmatched. Case Report: A 32-year-old female patient hailing to our hospital with the complaint of dyspnea, right upper abdominal pain, ascites, and bilateral pedal edema in May 2018. After proper investigation, she diagnosed with subacute right heart failure due to localized calcified CP. Therefore, she managed with diuretic therapy and symptomatic treatment. After one year, she suddenly present in the emergency department with the features of right heart failure. Her New York Heart Association (NYHA) score was class-III. After proper medical management of her symptoms, she underwent off-pump partial pericardiotomy with no complaints. Analgesics, Antibiotics, and diuretics were administered in the post-operative period. She was discharged on the 6th post-operative day with no symptoms of right heart failure. Conclusion: Herein, we report a very unusual presentation with localized CP, causing strangulation of heart, which had been treated successfully with off- pump partial pericardiotomy. Meticulous dissection is the key to a successful pericardiotomy.